Analyses of impact factors on human functional states in the Antarctic region - Gorgo, Yu. P.; Miroshnik, T. G.; Bogdanov, V. B.; Kharkovljuk, N. V.; Iljin, V. M. (Ukrainian Antarctic Journal, 2003)
There was studied the peculiar properties of human dynamic action in the Antarctic region. The main physiological parameters of winterers and season staff were examined. It was shown that at the beginning of the adaptation period considerable abnormalities in the humans health were not observed but a number of unstationary and metastable shapes increased.